Optimasi Elektroda Pada Sistem Pembangkit Plasma Non Termik untuk Meningkatkan Kuantitas Benih Mangrove - Azam, Much.; Hidayanto, Eko (BERKALA FISIKA, 2006)
The Mangrove is the tropics nature resources that has two aspects, economics and ecology. This plant can be iradiated by the corona discharge. It is need to radiate mangrove seed with nitrogen and analize it’s growt. For that have need optimations of the electrode on the non thermics plasma generator system in order to get the effective and the efficient radiations. The steps of the research are : analize system, make a prototype, test the prototype with simulations, compare the simulations result with the experiment result and analize the results. From the research can get conclution that: 1) had been succes to make prototype of the mangrove plant reproduction system by the corona discharge plasma technology with the point-plant electrode, 2) the simulations result show that electrical fields shall increase if the distance from electrode has been decreases, or the voltage of electrode has been incresed, or the distance among electrode has been decreased or the value of the electrode radius.has been opotimum, 3) the result of simulations show that the current density shall decrease if distance among electrode has been decreased, 4)for the same distance electrode, the electricel fields of the experiment results is bigger than the simulations result, because the value of permeability and permittivity medium on the simulation is using the value of the vaccum space. Key words : the non thermics plasma, iradition, Mangrove